The Efficacy and Safety of Probiotics for Allergic Rhinitis: A Systematic Review and Meta-Analysis - Luo, Chao; Peng, Shunlin; Li, Mao; Ao, Xudong; Liu, Zhiqing (Frontiers in Immunology, 2022)
Background Probiotics have proven beneficial in a number of immune-mediated and allergic diseases. Several human studies have evaluated the efficacy and safety of probiotics in allergic rhinitis; however, evidence for their use has yet to be firmly established. Objective We undertook a systematic review and meta-analysis aiming to address the effect and safety of probiotics on allergic rhinitis. Methods We systematically searched databases [MEDLINE (PubMed), Embase, and the Cochrane Central Register of Controlled Trials] from inception until June 1, 2021. Qualified literature was selected according to inclusion and exclusion criteria, the data were extracted, and a systematic review and meta-analysis was conducted. Results Twenty-eight studies were included. The results showed that probiotics significantly relieved allergic rhinitis symptoms (standardized mean difference [SMD], −0.29, 95% confidence interval (CI) [−0.44, −0.13]; p = 0.0003, I2 = 89%), decreased Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ) scores compared with the control group (SMD, −0.64, 95% CI [−0.79, −0.49], p < 0.00001, I2 = 97%), and increased T helper cell 1(Th1)/Th2 ratio (mean difference [MD], −2.47, 95% CI [−3.27, −1.68], p < 0.00001, I2 = 72%). There was no significant change in overall or specific IgE levels between probiotic-treated and placebo-treated subjects (SMD, 0.09, 95% CI [−0.16, 0.34], I2 = 0%, and SMD, −0.03, 95% CI [−0.18, 0.13], p = 0.72, I2 = 0%, respectively). Conclusions To sum up, probiotic supplement seems to be effective in ameliorating allergic rhinitis symptoms and improving the quality of life, but there is high heterogeneity in some results after subgroup analysis and clinicians should be cautious when recommending probiotics in treating allergic rhinitis. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, PROSPERO (CRD42021242645).